Prevalence and determinants of anemia among children aged from 6 to 59 months in Liberia: a multilevel analysis of the 2019/20 Liberia demographic and health survey data - Dagnew Getnet Adugna; Anteneh Ayelign Kibret; Hailu Aragie; Engidaw Fentahun Enyew; Gashaw Dessie; Mihret Melese; Wudneh Simegn; Endeshaw Chekol Abebe; Fitalew Tadele Admasu; Tadesse Asmamaw Dejenie (Frontiers Media S.A., 2023)
BackgroundAnemia is a serious worldwide public health issue that happens at any stage of life but primarily affects young kids and pregnant mothers. Although anemia has a significant impact on child health, its magnitude and associated factors in children aged 6-59 months have not been yet studied in Liberia. Therefore, the aim of this study was to identify the prevalence and determinants of anemia in children aged 6-59 months in Liberia.MethodsThe data was extracted from Liberia Demographic and Health Survey, conducted from October 2019 to February 2020. The sample was obtained using a stratified two-stage cluster sampling technique. An overall weighted sample of 2,524 kids aged 6-59 months was involved in the final analysis. We used Stata version 14 software for data extraction and analysis. A multilevel logistic regression model was employed to identify factors associated with anemia. Variables with a P-value of <0.2 in the bivariable logistic regression analysis were selected as candidates for multivariable analysis. In multivariable analysis, the adjusted odds ratios (AOR) with the 95% confidence interval (CI) were declared as the determinants of anemia.ResultsThe prevalence of anemia in children aged 6-59 months in Liberia was 70.8% [95% CI: 68.9%, 72.5%]. Of these, 3.4% were severe anemia, 38.3% were moderate anemia and 29.1% were mild anemia. Children aged 6-23 and 24-42 months, being stunted, children from households with unimproved toilet facilities, children from households with unimproved water sources, and lack of media (television) exposure were significantly associated with higher odds of anemia. However, using mosquito bed nets, living in the Northwestern and Northcentral region were significantly associated with lower odds of anemia among children 6-59 months.ConclusionIn this study, anemia in kids aged 6-59 months in Liberia was a main public health issue. Age of the child, stunting, toilet facility, water source, exposure to television, mosquito bed net use, and region were significant determinants of anemia. Therefore, it is better to provide intervention for the early detection and management of stunted children. Similarly, interventions should be strengthened to address unimproved water sources, unimproved toilet facilities, and lack of media exposure.